2008
DOI: 10.1002/adfm.200700931
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Gallium‐Doped Phosphate‐Based Glasses

Abstract: Novel quaternary gallium‐doped phosphate‐based glasses (1, 3, and 5 mol % Ga2O3) were synthesized using a conventional melt quenching technique. The bactericidal activities of the glasses were tested against both Gram‐negative (Escherichia coli and Pseudomonas aeruginosa) and Gram‐positive (Staphylococcus aureus, methicillin‐resistant Staphylococcus aureus, and Clostridium difficile) bacteria. Results of the solubility and ion release studies showed that these glass systems are unique for controlled delivery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
130
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 27 publications
7
130
0
1
Order By: Relevance
“…In fact, our own 71 Ga NMR study of CaONa 2 O-Ga 2 O 3 -P 2 O 5 melt-quenched glasses with a P/Ga > 9 detected only octahedral gallium. [6] High-energy X-ray diffraction data gives information on the structure of a material by revealing the correlations between the atoms present. The parameters that define these correlations, i.e.…”
Section: Structural Characterisationmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, our own 71 Ga NMR study of CaONa 2 O-Ga 2 O 3 -P 2 O 5 melt-quenched glasses with a P/Ga > 9 detected only octahedral gallium. [6] High-energy X-ray diffraction data gives information on the structure of a material by revealing the correlations between the atoms present. The parameters that define these correlations, i.e.…”
Section: Structural Characterisationmentioning
confidence: 99%
“…These results suggest that Gadoped PBG is a potentially promising new therapeutic agent for pathogenic bacteria including MRSA and C. difficile. [6] Here we have prepared Ga-doped PBG by a sol-gel route which, to the best of our knowledge, is the first report of such a preparation. The method is based upon that which we developed to prepare biocompatible, bioresorbable, sol-gel (CaO) 0.3 (Na 2 O) 0.2 (P 2 O 5 ) 0.5 glass [12] with the addition of gallium ethoxide as the Ga…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular our group has been very interested in the last few years in the substitution of MBGs by (i) up to 3.5% Ce2O3, because it was reported that Ce 3+ ions reduce the enamel demineralization, and are neuroprotective [19], (ii) up to 3.5% Ga2O3, because it was published that Ga 3+ ions increase the calcium content in bone, and are antimicrobial [20], and (iii) ZnO because, in addition to other biological functions, it was reported that Zn 2+ ions stimulates the bone formation and exhibit also a bactericide action [21,22]. In the …”
Section: Introductionmentioning
confidence: 99%
“…[16,[19][20][21][22][23][24][25][26] Other interesting materials are phosphate glasses, which have readily tuneable properties to improve cellular activity [27][28][29][30][31] or inhibit biofilm formation (antimicrobial glasses). [32][33][34] To date they were rarely used as polymer fillers. Glass fibers reinforced polymers have been shown to have highly desirable both biological and mechanical properties, therefore glass fillers as a powder/particles seem to be alternative for other used fillers.…”
mentioning
confidence: 99%